Diagnostic Accuracy of Splenoportal Index for Detection of Esophageal Varices in Patients of Liver Cirrhosis - Zeenat Saulat,Sana Wasim , Maria Khaliq, Bilal Altaf, Zeenat Saulat,Sana Wasim , Maria Khaliq, Bilal Altaf (Journal of Rawalpindi Medical College, 2019)
Background: To determine the diagnostic accuracy of splenoportal index for the prediction of esophageal varices in patients with cirrhosis Methods: In this cross sectional study patients(n= 75) having clinical and laboratory evidence of liver cirrhosis were selected. Sonographic findings of splenic index and portal vein velocity were correlated with the findings of endoscopic examination. P-value ≤ 0.05 considered as significant. Results were analyzed by creating 2 x 2 contingency tables which displayed the number of subjects who were positive on ultrasound and were also positive on endoscopy (true positives), who were ultrasound positive but were negative on endoscopy (false positives), who were ultrasound negatives but were positive on endoscopy (false negatives) and who were ultrasound negative and were also negatives on endoscopy (true negatives). Results: Majority ( 65.0%) patients were males. Patients positive on ultrasound were 70.7 % and patients positive on endoscopy were 72.0% . Sensitivity, specificity, positive predictive value, negative predictive value and accuracy were found to be 96.3%, 95.2%, 98.1%, 90.9% and 96% respectively. Conclusion: Ultrasonography allows non-invasive and cost effective detection of esophageal varices in liver cirrhosis patients, with excellent accuracy.